2016
DOI: 10.1002/wsb.634
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and risk probabilities of deer stand falls among Wisconsin hunters

Abstract: Falls from elevated hunting platforms have replaced firearm accidents as the largest source of hunting-related injuries and deaths in the United States. Our study applied participation and behavior data from 2 statewide hunter surveys conducted in 2013, current license purchasing data, and an audit of medical records between 2009 and 2013 in the north-central region of Wisconsin to generate annual and cumulative risk probabilities of being injured in a fall. Although archery hunting of deer (Odocoileus sp.) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In addition, they did not provide evidence that public attitudes of hunting and agency culling were similar. To the contrary, surveys done in both states have demonstrated that public acceptance of these types of killing is context-dependent and variable [ 12 , 13 ].…”
mentioning
confidence: 99%
“…In addition, they did not provide evidence that public attitudes of hunting and agency culling were similar. To the contrary, surveys done in both states have demonstrated that public acceptance of these types of killing is context-dependent and variable [ 12 , 13 ].…”
mentioning
confidence: 99%
“…Considering results from Walsh et al (2018) and our findings as a whole, intervals of highest predation risk occurred during times of greatest nutritional stress, predation rates and starvation rates were correlated, juvenile predation rates correlated with winter severity, and the markedly higher predation on juvenile deer relative to adult deer, suggested much of the predation observed in both studies was compensatory. This contradicts a common theory among deer hunters that wolves strongly limit deer abundance (Holsman et al 2014). Although we lack contemporaneous population estimates for all deer predators, variations in predator populations as extreme as variation reported by Walsh et al (2018) in juvenile predation rates (~10 times difference between the lowest and highest juvenile cumulative predation rates) are exceedingly unlikely.…”
Section: Discussionmentioning
confidence: 63%
“…Although the Iowa Department of Natural Resources has information on tree stand safety, 19 education on the use of safety harnesses to prevent falls from tree stands should be provided to all hunters. 20 Our study has several limitations, including its small sample size. First, the data were acquired through retrospective chart review, which introduces a risk of bias stemming from poor documentation or missing data.…”
Section: Discussionmentioning
confidence: 91%
“…Although the Iowa Department of Natural Resources has information on tree stand safety, 19 education on the use of safety harnesses to prevent falls from tree stands should be provided to all hunters. 20…”
Section: Discussionmentioning
confidence: 99%